Point-Based Grading System: Advantages and Disadvantages - N. N. Мaltseva; V. Е. Рenkov (Высшее образование в России)
One of the vital issues of modern education is assessing the level of students’ knowledge using a point-based grading system. Various approaches to definition of this phenomenon have been examined, and based on their analysis, the authors have come to the conclusion that the use of PBGS solves several important problems. First, it helps to evaluate students’ knowledge more accurately by increasing the maximum possible number of points. Second, it provides a possibility to evaluate individual work activities. Third, it encourages students to work hard to master new material throughout the semester. The authors have also scrutinized the disadvantages of this knowledge assessment system. These include: the risk of a biased judgment; fostering individualism when everyone is interested only in his/her personal growth; dominance of the written test over the oral answer; and the use of test tasks, which allows one to determine only the initial conceptual level of the subject without revealing the problematic, conceptual depth of knowledge, without identifying creative minds who can think outside the box. Then, through a mental experiment, various pedagogical situations have been assessed in which a formal use of a point-based grading system leads to biased results. The article proposes specific measures to improve the point-based grading system, so as to achieve a more objective assessment of competence level in students of higher educational institutions: 1) at least 50% of the total score should be planned for the final test event; 2) the final certification should include a small number of questions, which will allow, on the one hand, to save students’ time and effort, and, on the other, to master the material in depth; 3) dual accounting should be helpful – of the total number of points in the PBGS and of the final certification grades in the subject; 4) it is necessary to provide for an option to “transfer” points from one kind of work to another. In closing, the authors conclude that a point-based grading system has its own advantages and disadvantages, and, adhering to the above rules, it is possible to strengthen the former and weaken the latter. However, it should be emphasized that a complete switch to the PBGS and break with the traditional methods of testing knowledge seem inappropriate.